Amniotic Fluid β2- Microglobulin Measurements - Emine Aydın; Alp Tuna Beksaç; Ergün Karaağaoğlu; M. Sinan Beksaç (Gynecology Obstetrics & Reproductive Medicine, 2015)
OBJECTIVE: To determine β2-microglobulin levels in amniotic fluid during the course of second trimester.